Training of High Qualifications in the Accounting, Statistics Direction in Accordance with Professional Standards - Bychkova, Svetlana; Timoshenko, Svetlana (Buhalterinės apskaitos teorija ir praktika, 2018)
[full article and abstract in English] The human potential of science is the basis for the formation of the scientific elite, which has declined significantly in recent decades in Russia. The process of forming the human resources potential of a higher school science must begin with the qualitative organization of research activities of students. Then it is necessary to conduct training of scientific personnel in postgraduate study. At the final stage after graduation from the graduate school, it is necessary to carry out measures to secure the trained scientific personnel in higher education with the replacement of a certain post. The human resources potential of science should be considered as an integral characteristic of the available capabilities of each employee. It is important not only to properly assess this potential, but be able to form it. The training of highly qualified personnel is an important strategic stage in the formation of the human potential of science and increasing the competitiveness of the university, taking into account the presence of such negative factors as the aging of scientific personnel, the transfer of scientific and teaching staff to other spheres of the economy, etc. The competitiveness of a higher educational institution largely depends on postgraduate education, which significantly affects the rating indicators of the university. Objective of this research is carrying out a complex author’s research of the current state of training of the top skills in the Accounting, Statistics direction taking into account application of professional standards and also definition of positive and negative sides in the course of their interface. The research is conducted by means of the system analysis. The retrospective analysis of development of system of the higher education in Russia is also applied. The drawn conclusions confirm need of improvement of the existing system of the higher education in a number of the directions. It is necessary to understand that the personnel potential of science is the multidimensional category more difficult according to the contents, than the personnel capacity of the organization.